(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article tried to research the development of insurance activity in the Republic of Uzbekistan during the years of independence, dividing it into stages based on certain criteria. The main focus is on the analysis of the adopted legislative documents and statistical data on the development and regulation of insurance activities. Also, the article comments on the achievements and shortcomings in the reform and development of insurance activities over the past 30 years.